Estimasi Populasi dan Habitat Monyet Ekor Panjang (Macaca fascicularis Raffles, 1821) di Desa Ngesrepbalong, Jawa Tengah - S, Christine Nadya; Rahayuningsih, Margareta (Life Science, 2024)
Mount Ungaran leaves an important ecosystem as a habitat for various species, including long-tailed macaques (Macaca fascicularis Raffles, 1821). Long-tailed macaques (MEP) are a type of animal that is not protected according to PP No. 106 of 2018. In the IUCN, the conservation status of MEP has changed from the vulnerable category to endangered and is included in Appendix II based on CITES. Estimation of the population of a species is very necessary to provide an overview of the existence of the species in an area. There has been no research on the estimation of the population and habitat of MEP in Ngesrepbalong Village. The purpose of this study was to analyze the estimation of the MEP population and the condition of the MEP habitat in Ngesrepbalong Village, Central Java. The method used in this study was the survey method with the calculation of concentration points (concentration count). This method is used on various types of wild animals that gather in groups at observation points that have been previously determined based on the results of preliminary surveys along with the habitat conditions analyzed to produce an estimate of the MEP population and habitat at the research location. The results of the analysis of the estimated MEP population in Ngesrepbalong Village found 53 individuals in two groups at two observation points, namely Gunungsari and Separe with the percentage of the MEP population based on sex, namely 28% juveniles, 38% juveniles, and 34% adults. The increasing number of young MEP individuals indicates that the population will increase assuming a constant mortality rate. Poaching and habitat carrying capacity are the most influential factors in the difference in population numbers at the two observation points. The highest MEP encounters were at the Gunungsari observation point.